PERSPEKTIF GEOLOGI RUANG-RUANG DI KOMPLEKS SITUS GUA MAROS - M. Fadhlan S. Intan (WalennaE, 2001)
Cave was the medium for prehistorically human to sheltered and to avoided from the difficulties, which were caused by the nature. The establishment of the caves in Maros limestone area was started since the carbonate was sedimentatedin submarine. Based on the geological structure, Maros limestone cave is divided into two, i.e. tightpole (kekar tiang) cave and tightpage (kekar lembaran) cave with its own room characteristics. The geological structure of the cave room is very influence the conservation of the archaeological inheritance and the amount of the cave that-present can be shown.